GREEN SYNTHESIS OF SILVER NANOPARTICLES USING OCIMUM SANCTUM L. AND OCIMUM AMERICANUM L. FOR THEIR ANTIBACTERIAL POTENTIAL: Pharmaceutical Sciences-Nanotechnology - YADAV, ANITA; KAUSHIK, AASHIMA; JOSHI, ANUJA (International Journal of Life Science and Pharma Research, 2018)
Development of green nanotechnology is generating interest of researchers toward eco-friendly biosynthesis of nanoparticles. In this study, biosynthesis of stable silver nanoparticles was done using Tulsi (Ocimum sanctum L. and Ocimum americanum L.) leaf extract. These biosynthesized nanoparticles were characterized by different techniques including UV–Vis spectrophotometer, Fourier transform infrared spectroscopy (FTIR) and Scanning electron microscopy (SEM). The surface plasmon resonance (SPR) absorption band obtained at 408 in Ocimum americanum L. and 427 nm in Ocimum sanctum L. reveals the reduction of silver metal ions into silver nanoparticles. FT-IR analysis was carried out to probe the possible functional group involved in the synthesis of AgNPs. SEM results indicated that AgNPs were predominantly spherical in shape with a particle size of 40-95 nm. Further biosynthesized AgNPs were evaluated for antibacterial activity by disc diffusion method against Gram-negative (Escherichia coli, Klebsiella pneumoniae and Pseudomonas aeruginosa) bacteria. The leaf extract of O. sanctum L. showed height antibacterial activity (6.56±0.15) againstEscherichia coli. This recent research study opens an innovative design to progress our understanding of how SNPs behave can be optimized to improve human antimicrobial activities.